2016
DOI: 10.5137/1019-5149.jtn.17347-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for recurrence of chronic subdural hematoma

Abstract: Within the scope of this study, we detected aphasia and separated cSDH as predictors of cSDH recurrence. Homogeneous isodense cSDH seems to be a good prognostic sign regarding the risk of recurrence development. Furthermore, our data clearly emphasize the importance of surgically applied drainage implants to prevent a recurrence of cSDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
3
25
0
1
Order By: Relevance
“…Overall, we found a higher recurrence risk in laminar and separated hematoma than in other hematomas. Several individual studies, however, did not report a high recurrence rate in laminar hematoma [29,43,64], but did report trabecular hematoma, corresponding to hematoma with multiplicity of cavities, to reoccur more often [49,[65][66][67][68][69]. This variation and discrepancy is most likely caused by the many available architecture categories which are applied parallel to the classification of Nakaguchi (i.e., loculated hematoma, hematoma with multiplicity of cavities, layered type hematoma, organized hematoma, and niveau formation), but OAC oral anticoagulation, PAI platelet aggregation inhibitor, reCSDH CSDH recurrence a Four patients died before discharge, therefor analyses were performed in 457 patients b Two patients died before discharge, therefor analyses were performed in 246 patients c Because of rounding, percentages in combined "OAC or PAI" group may differ with one percent from the sum of "OAC" and "PAI" could also be due to difficulties in applying the classification correctly [18,26,45,59,70,71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we found a higher recurrence risk in laminar and separated hematoma than in other hematomas. Several individual studies, however, did not report a high recurrence rate in laminar hematoma [29,43,64], but did report trabecular hematoma, corresponding to hematoma with multiplicity of cavities, to reoccur more often [49,[65][66][67][68][69]. This variation and discrepancy is most likely caused by the many available architecture categories which are applied parallel to the classification of Nakaguchi (i.e., loculated hematoma, hematoma with multiplicity of cavities, layered type hematoma, organized hematoma, and niveau formation), but OAC oral anticoagulation, PAI platelet aggregation inhibitor, reCSDH CSDH recurrence a Four patients died before discharge, therefor analyses were performed in 457 patients b Two patients died before discharge, therefor analyses were performed in 246 patients c Because of rounding, percentages in combined "OAC or PAI" group may differ with one percent from the sum of "OAC" and "PAI" could also be due to difficulties in applying the classification correctly [18,26,45,59,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies reported on uni-and bilaterality with incomplete data in two [43,44], resulting in seventeen studies with a total of 4400 patients for laterality analysis with a high study heterogeneity (I 2 = 70%). Patients with bilateral CSDH had higher hematoma recurrence than patients with a unilateral CSDH (Fig.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…The number of recurrences was acceptable – 3.5% required repeated surgery. All patients had control CT 3 to 5 days after initial surgery, however it does not seem necessary [14], and control CT should be performed only in patients, whose clinical status worsens after initial surgical treatment. In 73 (10.5%) patients control CT showed significant pneumocephalus, however no one patient presented clinical symptoms or required surgical treatment due to this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma density has also been cited by many authors as a risk factor for recurrence. 12 , 20 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Some prospective studies showed no beneficial effect, whereas other authors report lower recurrence rates with the use of postoperative drains because of brain expansion. 3 , 8 , 22 , 24 , 25 A recent meta-analysis concluded that postoperative drainage is clearly useful in the treatment of CSDH and should be recommended. 2 Our findings also corobrate this conclusion as post operative drainage significantly (p<0.05) reduced the CSDH recurrence rate in our study.…”
Section: Discussionmentioning
confidence: 99%